2022
DOI: 10.3389/fnut.2022.790250
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic and Eicosapentaenoic Intervention Modifies Plasma and Erythrocyte Omega-3 Fatty Acid Profiles But Not the Clinical Course of Children With Autism Spectrum Disorder: A Randomized Control Trial

Abstract: BackgroundThe pathogenesis of autism spectrum disorder (ASD) is under investigation and one of the main alterations relates to the metabolic and inflammatory system dysfunctions. Indeed, based on a possible deficit of omega-3 fatty acids (FAs) of patients with ASD and looking for an anti-inflammatory effect, dietary supplements with omega-3 fatty acids have been proposed. We aimed to evaluate differences in plasma and erythrocyte FA profiles and plasma cytokines in patients with infantile ASD after supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…Another open-label study of EPA and DHA supplementation (190 mg of EPA acid and 90 mg of DHA per 500 mg capsule; 2 capsules per day) on ten ASD children showed an improvement on the Autism Treatment Evaluation Checklist [40]. However, a recent double-blind, randomized placebo-controlled study on 54 ASD children showed that supplementation for 6 months with ω-3 FAs (including 800 mg/day of DHA and 25 mg/day of EPA) had no impact on clinical test scores [41].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another open-label study of EPA and DHA supplementation (190 mg of EPA acid and 90 mg of DHA per 500 mg capsule; 2 capsules per day) on ten ASD children showed an improvement on the Autism Treatment Evaluation Checklist [40]. However, a recent double-blind, randomized placebo-controlled study on 54 ASD children showed that supplementation for 6 months with ω-3 FAs (including 800 mg/day of DHA and 25 mg/day of EPA) had no impact on clinical test scores [41].…”
Section: Discussionmentioning
confidence: 96%
“…Another double-blind placebo-controlled study of ω-3 FA supplementation with 600 mg EPA and 120 mg DHA for 16 months improved the working memory function in 55 ADHD children [43]. The studies on ASD and ADHD suggest that various ratios of EPA to DHA in ω-3 FA supplements have inconsistent effects on the clinical profile [41,43,44]. DHA and EPA are structural components of cell membranes in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial indicated that omega‐3 fatty acids improve the fatty acid composition of erythrocyte membranes but do not alter the status of antioxidants in plasma and do not have significant therapeutic effects on ASD‐like phenotypes (Parellada et al., 2017). In addition, a double‐blind placebo‐controlled study found that a 6‐month intervention with docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) did not improve clinical symptoms and did not have anti‐inflammatory effects in children with ASD (de la Torre‐Aguilar et al., 2022). In the future, large‐scale randomized controlled trials of various polyunsaturated fatty acids with potential ASD‐mitigating effects are needed to determine whether they have the desired effects and to provide research direction for molecular mechanism analyses in animal models.…”
Section: Food‐derived Nutrients That Have Effects On Asdmentioning
confidence: 99%
“…EPA and DHA are found in natural foods and are mainly supplemented through diet or deep-sea fish oil [7]. DHA plays a role in cognitive function, neurotransmission, neuronal survival and attenuating neurodegeneration [8]. The balance of essential fatty acids is essential for brain development and considered as a possible biomarker for ASD [9].…”
Section: Introductionmentioning
confidence: 99%